Performance-Based Accounting and Its Influence on Employee Motivation - Rusdiah Hasanuddin; Nurasia Natsir; Nadya Nurhidayah Nurdin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study investigates the relationship between performance-based accounting practices and employee motivation within organizations. Utilizing a quantitative research design, a survey was conducted among employees in a specific industry to analyze how performance measurement systems impact motivation levels. The sample included 200 employees in PT. Pabrik TERIGU Makassar, and data were collected on their perceptions of performance-based accounting practices, such as clarity of performance metrics and reward systems. Statistical analyses, including linear regression and correlation analysis, revealed a significant positive correlation between effective performance-based accounting and increased employee motivation. The findings suggest that organizations that implement clear performance metrics and recognition programs can enhance employee engagement and productivity. This study contributes to the existing literature by providing empirical evidence of the positive influence of performance-based accounting on employee motivation, highlighting practical implications for management practices aimed at fostering a motivated workforce.